Sex chromosomes in mitotic and polytene tissues of Anastrepha fraterculus (Diptera, Tephritidae) from Argentina: a review - Giardini, Maria Cecilia; Milla, Fabian Horacio; Lanzavecchia, Silvia Beatriz; Nieves, Mariela; Cladera, Jorge Luis (Pensoft Publishers, 2021)
Cytogenetics, which is considered a fundamental tool to understand basic genetic and genomic issues of species, has greatly contributed to the description of polymorphisms both at inter- and intra-specific level. In fact, cytogenetics was one of the first approaches used to propose Anastrepha fraterculus (Diptera: Tephritidae) as a complex of cryptic species. Different morphological variants of sex chromosomes have been reported among Argentinean populations of Anastrepha fraterculus. However, since this high structural variability in sex chromosomes does not pose a reproductive barrier, their role in speciation is yet to be unveiled. This review provides an update on general aspects of cytogenetics in Argentinean Anastrepha fraterculus populations, focused on the prevalence of X-Y arrangements.